Proteomic Analysis of Wild-Type Sinorhizobium meliloti Responses to N-Acyl Homoserine Lactone Quorum-Sensing Signals and the Transition to Stationary Phase - Chen, Hancai (American Society for Microbiology, 2003)
Proteome analysis revealed that two long-chain N-acyl homoserine lactones (AHLs) produced by Sinorhizobium meliloti 1021 induced significant differences in the accumulation of more than 100 polypeptides in early-log-phase cultures of the wild type. Fifty-six of the corresponding proteins have been identified by peptide mass fingerprinting. The proteins affected by addition of these two AHLs had diverse functions in carbon and nitrogen metabolism, energy cycles, metabolite transport, DNA synthesis, and protein turnover. Two hours of exposure to 3-oxo-C(16:1)-homoserine lactone (3-oxo-C(16:1)-HL) affected the accumulation of 40 of the 56 identified proteins, whereas comparable exposure to C(14)-HL affected 13 of the 56 proteins. Levels of four proteins were affected by both AHLs. Exposure to 3-oxo-C(16:1)-HL for 8 h affected the accumulation of 17 proteins, 12 of which had reduced accumulation. Of the 80 proteins identified as differing in accumulation between early-log- and early-stationary-phase cultures, only 13 were affected by exposure to 3-oxo-C(16:1)-HL or C(14)-HL. These results provide a foundation for future studies of the functions regulated by AHL quorum sensing in S. meliloti and help to establish proteomic analysis as a powerful global approach to the identification of quorum-sensing regulatory patterns in wild-type bacteria.